Comparative Analysis of Indicated Abandoned Land Utilization for Vulnerable Community Empowerment and Legal Justice - Permata Intan Maharani; Rini Fidiyani (Universitas Negeri Semarang, 2026)
Land plays a vital role in supporting social welfare and economic development within communities. Under Indonesian agrarian law, land must fulfill a social function; however, in practice, there remains land that is not being optimally utilized, while vulnerable communities still face limited access to agrarian resources. In this context, land suspected of being abandoned becomes significant as a potential starting point for land utilization by the community. This study aims to analyze the government’s responsibility in ensuring access to land utilization, particularly for land indicated as abandoned, for vulnerable communities as an effort to realize legal justice, as well as to compare its implementation in South Jakarta Administrative City and Semarang City. This study employs a qualitative approach using a sociological-legal methodology through interviews and literature review. The research findings indicate that the government has a constitutional responsibility to ensure access to agrarian resources, which encompasses not only the utilization of abandoned land but also the optimization of the identification of land suspected of being abandoned. Empirically, in the City of Semarang, there are 7 plots of land suspected of being abandoned, while in the South Jakarta Administrative City, there are 2 plots that have not yet been optimally addressed. A comparison indicates that the utilization of land suspected of being abandoned has not yet become the primary instrument for empowering vulnerable communities in urban areas. Therefore, empowerment is more frequently achieved through alternative policies such as land certification, asset legalization, and economic empowerment. Consequently, land policies must be tailored to regional characteristics to achieve social justice and community well-being.